The experiences and psychological impact of living with premenstrual disorders: a systematic review and thematic synthesis - Brown, Danielle; Smith, Debbie M.; Osborn, Elizabeth; Wittkowski, Anja (Frontiers in Psychiatry, 2024)
As the psychological impact and decreased quality of life experienced by women living with a Premenstrual Disorder (PMD) has been reported in the literature, the aim of this systematic review and thematic synthesis was to explore a) their experiences and the psychological impact of PMDs, specifically Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Disorder (PMDD), and b) their perceived support needs. Method: Six databases were searched for publications reporting on qualitative studies, since the database inception. The Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines were followed, and Thomas and Harden's (2008) thematic synthesis method was used. Results: Seventeen papers reporting on 479 women met the inclusion criteria: ten focused on PMS, six on PMDD and one on PMS and PMDD combined. Two main PMD themes were identified: 1) controlled by PMDs, which had three subthemes, and 2) a women and life left broken, with five subthemes. Conclusion: Women's accounts revealed that experiences of PMDs were intense, life changing and life-controlling. Women were left holding the responsibility of understanding and managing their own condition, whilst advocating for themselves in a healthcare setting in which their condition has been little understood. Consequently, women developed coping strategies to lead a functional life, and experienced changes to their sense of self. Clinical recommendations included the need for professionals working with women in crisis, to assess for PMDs and signpost towards specialist services.